Correlation of Aspergillus fumigatus Sensitization with Mucus Plugging in COPD - Luo Y; Ren J; Liang L; Qu J; Chang C; Sun Y (International Journal of COPD)
Ying Luo,1,2 Jiaqi Ren,1,2 Long Liang,1,2 Jingge Qu,1,2 Chun Chang,1,2 Yongchang Sun1,2 1Department of Respiratory and Critical Care Medicine, Peking University Third Hospital, Beijing, People’s Republic of China; 2Research Center for Chronic Airway Diseases, Peking University Health Science Center, Beijing, People’s Republic of ChinaCorrespondence: Chun Chang; Yongchang Sun, Email doudou_1977@163.com; suny@bjmu.edu.cnBackground: Both Aspergillus fumigatus sensitization and mucus plugs are associated with poor clinical outcomes in COPD. However, little is known about the association between Aspergillus hypersensitivity and mucus plugging in patients with COPD.Methods: We retrospectively enrolled COPD patients who had visited Peking University Third Hospital and received measurement of the Aspergillus Fumigatus specific IgE (Af sIgE) from Oct 1, 2018 to Sep 30, 2023. The clinical, laboratory, and chest CT features were analyzed, with mucus plugging evaluation using the bronchopulmonary segment-based scoring system. Comparison was performed between COPD patients with and without Aspergillus hypersensitivity (AH).Results: Among the 378 COPD patients with measurement of Af sIgE, 29 (7.7%) were classified as having AH (Af sIgE> 0.35KU/L). By propensity score matching (1:2), 58 patients without AH were included for comparison. Patients with AH had lower FEV1%pred (P=0.008) and FEV1/FVC (%) (P=0.023), and were more likely to have a blood eosinophil count exceeding 300/μL and higher white blood cell and neutrophil counts. The prevalence of luminal plugging on chest CT in subjects with AH was 58.6%, compared to 31.0% in those without AH (P=0.013). Multivariate regression analyses showed that Af sIgE more than 0.70 KU/L and blood neutrophil count were associated with mucus plugging.Conclusion: In patients with COPD, Aspergillus sensitization was associated with lower lung function and mucus plugging on chest CT.Keywords: COPD, Aspergillus fumigatus, hypersensitivity, mucus plug